Diabetes mellitus tipo 2 y toxicidad por quimioterapia en adultos mayores con cáncer prostático - Runzer-Colmenares, Fernando M. (2019)
ABSTRACT Introduction: Prostate cancer is considered a predominant type of neoplasia and aging is a factor for chemotherapeutic toxicity, which can increase due to chronic diseases, particularly diabetes. Despite all this knowledge, there are no studies to evaluate the association between diabetes and the risk of chemotherapeutic toxicity in these patients. Objective: To determine the association between Type 2 Diabetes Mellitus and the risk of chemotherapy toxicity in in older adults with prostate cancer in the Geriatric Service of the Peruvian Naval Medical Center. Material and methods: Analytical retrospective cohort study and secondary database analysis. The adverse effects of chemotherapy and the associated factors of 161 retired sailors with prostate cancer were evaluated between 2013 and 2015. Cox Regression Model for Adjusted Toxicity was constructed for antecedents of diabetes, age, pathological antecedents, smoking antecedents, calf circumference, physical activity, dependence on ABVD, falls, polypharmacy, fragility, and vulnerability. Results: The 23.6% of patients had diabetes. The prevalence of fragility was 39.7% and the one of vulnerability was 24.2% (G8) and 26.71% (VES-13). The frequent adverse effects were: gastrointestinal (13.04%) and hematological (8.07%). The most significant associations by adjusted regression model were the antecedent of Type 2 Diabetes Mellitus, 3 or more pathological antecedents, smoking antecedents, calf circumference, physical activity, dependence on ABVD, falls, polypharmacy, fragility, and vulnerability. Conclusions: The antecedent of Type 2 Diabetes Mellitus is a predictive factor for the risk of chemotherapy toxicity in older adults with prostate cancer.